Penerapan Media Poster Berbasis STEAM dalam Meningkatkan Kemampuan Berpikir Siswa UPT TK Pembina 01 Pancung Soal - Muhammadi Muhammadi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
The development of children's thinking skills is greatly influenced by learning methods as well as enthusiasm that encourages all forms of intellectual progress and social interaction skills. This article examines the application of poster media based on the STEAM learning approach at TKN 01 Pancung Soal, South Pesisir Regency, West Sumatra Province. This study includes qualitative research which is arranged in several stages of research, namely source collection, data analysis and interpretation. There are two types of sources used, primary sources which are primary or principal sources and secondary sources or sources of comparative research. Primary sources include school data such as establishment archives, board members, student names and so on as well as interview data obtained during the research. While secondary data is similar research that has been published in online journal media. This study concluded that the application of STEAM-based poster media has a major influence on children's thinking development abilities, especially in three aspects, namely increasing the ability to think, socialize and interact. Then from the pragmatic side, the application of poster media also has high effectiveness in children's learning and is easier to obtain.